Model Pengaruh Persepsi Terhadap Kepuasan dan Loyalitas Pemustaka di Perpustakaan Nasional Republik Indonesia (Models Influence Perceptions to Satisfaction and Loyalty Library Users in National Library of The Republic of Indonesia) - Leli Tamara; M. Syamsun; Ma'mun Sarma (Jurnal Sains Terapan : Wahana Informasi dan Alih Teknologi Pertanian, 2014)
Improvement of service quality should be done consistently. Services of the National Library of the Republic of Indonesia should be based on the principle of public service. Efforts to improve the service factor will help deliver satisfaction and value -added library. Therefore, this research aimed to analyze influence perceptions to satisfaction and loyalty library user’s in National Library of The Republic of Indonesia. This research was conducted at the National Library of the Republic of Indonesia on closed access services. Methods of testing instruments used were SPSS Software 16.00 and hypothesis testing used structural equation modeling (SEM) by software SmartPLS 2.00. Characteristics of respondents predominantly female (68%), aged 17-25 years (82%), working as a student (79%) and educated S1 (76 %). Based on the analysis of SEM with PLS approach, we can see the influence of the six basic elements of the library (electronic resources, print publications, other services, technical facilities, library environment, human side) to the value, satisfaction and loyalty. The results showed, the other services have a significant influence with the value of the users in the National Library of the Republic of Indonesia. While the variables of human side, environmental and electronic library resources influenced to satisfaction in the National Library of Indonesia. While the value of users variables significantly influenced to loyalty in the National Library of the Republic of Indonesia. Therefore it can be concluded that not all of the basic elements of the library have influence to value, satisfaction and loyalty.Keywords : quality of service, value, satisfaction , loyalty, partial least squares (PLS)